Experimental and numerical investigation on the dynamic response of steel chamber under internal blast. (1st August 2018) - Yao, Shujian; Zhang, Duo; Lu, Zhaijun; Lin, Yuliang; Lu, Fangyun
Highlights: Blast tests of a series of steel chambers with different size. DIC technique is applied to record the dynamic response process. Deformation features of experimental and numerical results. "Five mountains" deformation shape occurs during the process. Abstract: The present work aims at investigating the dynamic response of steel chamber under internal blast loading through both experiments and numerical simulations. In the experiment, digital image correlation (DIC) technique is applied to record the three-dimensional (3D) displacement and dynamic response process. A series of steel chamber specimens with different size were designed to conduct internal blast tests, and then numerical models were built by using ANSYS/LS-DYNA. The 3D deformation features were analyzed through both experimental and numerical results. The results show that outward bulging occurs in all side plates and in-plane buckling takes place in all boundary plates. Furthermore, plastic hinge lines along the two diagonals of the target side plate are observed. In addition, 3D dynamic response processes were analyzed through both the DIC technique and numerical results. "Five mountains" deformation shape was observed during the response process because of the confinement of chamber corner to the blast wave. The dynamic response results indicate that the response process of the side plate includes two stages: the whole plate plastic response stage and the central area oscillating stage. In a word, the results confirm that DIC technique is capable of accurately measuring full-field dynamic response of structures under blast loading, and the numerical method established in the present study is efficient and effective in modeling dynamic problems.